Cultivation of Microalgae in Unsterile Malting Effluent for Biomass Production and Lipid Productivity Improvement - Janak Raj Khatiwada; Haipeng Guo; Sarita Shrestha; Chonlong Chio; Xuatong Chen; Aristide Laurel Mokale Kognou; Wensheng Qin (Fermentation, 2022)
Microalgae have the potential to grow in nutrient-rich environments and have the ability to accumulate nutrients from wastewater. The nutrients in malting wastewater are ideal for microalgae cultivation. However, there is limited published work on the growth characteristics of freshwater microalgae grown in malting effluent. This study examined the potential of diluted malting effluent for the growth of freshwater green algae Chlorella sp. and Chlamydomonas sp. isolated from northern Ontario and subsequent biomass and lipid production. Under the 18:6 h light/dark cultivation cycle, the highest cell number counted (540 × 104 cell·mL−1 on day 20) and total chlorophyll content were found in 50% diluted malting effluents for Chlorella sp., whereas the 70% dilution concentration was the most productive for Chlamydomonas (386 × 104 cell·mL−1 on day 16). The total lipid content was higher in the 50% dilution concentration of malting effluent in both Chlorella sp. (maximum 20.5%–minimum 11.5% of dry weight) and Chlamydomonas sp. (max 39.3%–min 25.9% of dry weight). These results emphasize the suitability of using unsterile diluted malting effluent for microalgae cultivation.